Gestational age Estimated by Abdominal Circumference in Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Objective: Abdominal circumference measurement is an important parameter for determining  fetal growth. Fetal growth will be more accurately assessed if we use tables constructed on  our own population. A table of fetal gestational age estimation by abdominal circumference in  Bangladeshi population is prepared, so that a quick assessment of its growth can be made.Methods: This study was a prospective, cross-sectional study, conducted on well dated, singleton  pregnancies. A table and a graph were prepared after fitting Polynomial regression models.Results: Nomogram for gestational age estimation by abdominal circumference was prepared.  1223 patients were included in the study. Percentiles, mean and standard deviations were  derived from the raw data. Polynomial regression model was a good fit to the data. Standard  deviations increased with gestational age. In the early second trimester Bangladeshi and  western studies were similar but as pregnancy advanced there was variation between the two  races.Conclusion: This chart can be useful for Bangladeshi population, by helping in assessment of  fetal growth and gestational age by abdominal circumference, especially in the 3rd trimester.  This is so, because abdominal circumference is very sensitive to fetal nutritional status. DOI: http://dx.doi.org/10.3329/bjog.v26i2.13781 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(2) : 64-67